5-fluorouracil enhances the antitumor effect of sorafenib and sunitinib in a xenograft model of human renal cell carcinoma - MIYAKE, MAKITO (D.A. Spandidos, 2012)
Sorafenib and sunitinib are multi-kinase inhibitors with antitumor activity in patients with advanced renal cell carcinoma (RCC). Several studies have evaluated the effect of sorafenib/sunitinib in combination with chemotherapeutic agents in different types of tumor. However, few studies have addressed the activity of fluorinated pyrimidine in combination with sorafenib/sunitinib. In this study, we examined the potential of combination therapy with 5FU and sorafenib/sunitinib in human RCC cell lines. Three human RCC cell lines, ACHN, Caki-1 and Caki-2, were used to assess sensitivity to 5-fluorouracil (5FU), sorafenib and sunitinib alone or in combination using an in vitro cell survival assay. Caki-2 cells demonstrated significantly higher resistance to 5FU and sorafenib as compared to ACHN and Caki-1. Additive antitumor effects of the combination therapy were observed in the in vitro study. There was a tendency for a positive correlation between the sensitivity to sunitinib and platelet-derived growth factor β (PDGFR-β) expression levels, which were examined by reverse transcription polymerase chain reaction. Caki-1 xenograft models were prepared by inoculating cells subcutaneously into nude mice, which were divided randomly into six groups: control, 5FU (8 mg/kg/day, intraperitoneally), sorafenib (15 mg/kg/day, orally), sunitinib (20 mg/kg/day, orally), and 5FU with sorafenib or sunitinib. The treatments were administered on 5 days each week, and tumor growth was monitored for 42 days following inoculation of cells. Synergistic antitumor effects of the combination therapy were observed in an in vivo study. The resected tumors were evaluated using the Ki-67 labeling index and microvessel density. Both the Ki-67 labeling index and microvessel density were decreased in tumors treated with the combination therapy compared to those treated with sorafenib/sunitinib alone. These findings suggest that the combination therapy of 5FU with sorafenib/sunitinib may be an effective therapeutic modality for advanced RCC patients.